2021
DOI: 10.1186/s12576-021-00805-1
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory bulb modulates entorhinal cortex oscillations during spatial working memory

Abstract: Cognitive functions such as working memory require integrated activity among different brain regions. Notably, entorhinal cortex (EC) activity is associated with the successful working memory task. Olfactory bulb (OB) oscillations are known as rhythms that modulate rhythmic activity in widespread brain regions during cognitive tasks. Since the OB is structurally connected to the EC, we hypothesized that OB could modulate EC activity during working memory performance. Herein, we explored OB–EC functional connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The EC-dHPC is a critical circuit for object recognition 17 , 32 . Moreover, the OB is closely connected with hippocampal formation, particularly EC, a hub for the hippocampus 28 , 33 , 34 . Initially, we found that coherence and synchrony of the EC-dHPC circuit are decreased in Aβ animals compared to the control group at theta and gamma bands during NOR task performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EC-dHPC is a critical circuit for object recognition 17 , 32 . Moreover, the OB is closely connected with hippocampal formation, particularly EC, a hub for the hippocampus 28 , 33 , 34 . Initially, we found that coherence and synchrony of the EC-dHPC circuit are decreased in Aβ animals compared to the control group at theta and gamma bands during NOR task performance.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly , OB rhythmic activity dynamically modulates other brain areas, notably the EC-dHPC, during a cognitive performance 28 . Thus, disrupted coupling due to Aβ in this circuit, probably via its direct effect on OB synapses and regardless of neural loss, may be responsible for impaired recognition memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signals were preprocessed using the EEGLAB toolbox for noise rejection and baseline correction. 12 Power spectral density (PSD) was computed using the Welch's periodogram function in MATLAB. 30 To plot connection edges within five brain regions, we first calculated the coherence using mscohere function in MATLAB, and then any pairwise regions that passed the designated threshold of coherence were connected.…”
Section: Signal Processingmentioning
confidence: 99%
“…8,9 The OB is intricately connected to limbic regions and plays a role in memory control within a network involved memory-related functions. [10][11][12] The EC acts as the gateway for information entering and exiting the hippocampus. 13 It also serves as an interface between the medial prefrontal cortex (mPFC) and HPC for the rapid encoding of new memories.…”
Section: Introductionmentioning
confidence: 99%